THE FOREST AS A KEY ELEMENT FOR SUSTAINABLE DEVELOPMENT AND IMPROVED QUALITY OF LIFE IN CITIES – SELECTED PROBLEMS AND EXAMPLES - Anna Martyka; Joanna Figurska-Dudek (Journal of Civil Engineering, Environment and Architecture, 2023)
This article focuses on the role of green and blue infrastructure, including forests, in the context of urban planning and sustainable urban development. Using an interdisciplinary approach, the authors highlight theoretical frameworks on resource management, ethics and efficiency in architecture and construction. The remainder of the paper examines practical strategies for sustainable urban development, including the application of natural solutions and resource-saving systems. The case study shows real-life examples such as the 'Madrid Metropolitan Forest' or applications in Poland, including Sopot, where greenery plays a key role in the quality of life of residents and adaptation to climate change. The article highlights that integrated green urban spaces have benefits on many levels - from energy efficiency to social well-being and public health. The authors point to a growing body of evidence demonstrating the effectiveness of nature-based solutions in the context of challenges such as urbanisation and climate uncertainty. Long-term integrated urban planning that considers these aspects is key to creating sustainable and resilient cities